Noise properties of an optical frequency comb from a SESAM-modelocked 1.5 µm solid-state laser stabilized to the 10 -13 level - Schilt, Stephane; Dolgovskiy, Vladimir; Bucalovic, Nikola; Schori, Christian; Stumpf, Max C.; Di Domenico, Gianni; Pekarek, Selina; Oehler, Andreas E. H.; Südmeyer, Thomas; Keller, Ursula; Thomann, Pierre (My University, 2012)
We present a detailed investigation of the noise properties of an optical frequency comb generated from a femtosecond diode-pumped solid-state laser operating in the 1.5-μm spectral region. The stabilization of the passively mode-locked Er:Yb:glass laser oscillator, referred to as ERGO, is achieved using pump power modulation for the control of the carrier envelope offset (CEO) frequency and by adjusting the laser cavity length for the control of the repetition rate. The stability and the noise of the ERGO comb are characterized in free-running and in phase-locked operation by measuring the noise properties of the CEO, of the repetition rate, and of a comb line at 1558 nm. The comb line is analyzed from the heterodyne beat signal with a cavity-stabilized ultra-narrow-linewidth laser using a frequency discriminator. Two different schemes to stabilize the comb to a radio-frequency (RF) reference are compared. The comb properties (phase noise, frequency stability) are limited in both cases by the RF oscillator used to stabilize the repetition rate, while the contribution of the CEO is negligible at all Fourier frequencies, as a consequence of the low-noise characteristics of the CEO-beat. A linewidth of ≈150 kHz and a fractional frequency instability of 4.2×10−13 at 1 s are obtained for an optical comb line at 1558 nm. Improved performance is obtained by stabilizing the comb to an optical reference, which is a cavitystabilized ultra-narrow linewidth laser at 1558 nm. The fractional frequency stability of 8 × 1014− at 1 s, measured in preliminary experiments, is limited by the reference oscillator used in the frequency comparison.